Enterotoxigenic Escherichia coli Interferes FATP4-Dependent Long-Chain Fatty Acid Uptake of Intestinal Epithelial Enterocytes via Phosphorylation of ERK1/2-PPARγ Pathway - Li, Zhi; Liu, Heyuan; Xu, Bocheng; Wang, Yizhen (Frontiers in Physiology, 2019)
Sufficient fatty acid (FA) uptake from jejunal lumen is closely associated with pediatric growth. Enterotoxigenic Escherichia coli (ETEC), which poses a big threat to young mammals’ health, is also targeted on the jejunum, however the effects on FA uptake is not understood yet. To explore the impacts of ETEC on the FA uptake ability of jejunum epithelial enterocytes during early life, we orally gavaged weaning piglets with ETEC K88 and found intestinal inflammation combined with compromised uptake of LCFA (C16:0, C18:0, C20:3, C20:4) except for C14:0 whose chain length is similar to medium chain fatty acid (MCFA). Furthermore, we observed reduced protein expression of tight junctions (TJs), fatty acid transport protein 4 (FATP4), peroxisome proliferator-activated receptor γ (PPARγ), phosphorylated extracellular signal-regulated kinase 1/2 (p-ERK1/2), and upregulated expression of p-PPARγ. In the in vitro study, we challenged polarized porcine intestine jejunum cell line IPEC-J2 with ETEC K88 and discovered similar results on intestinal barrier and expression of associated genes combined with morphological changes. Based on the constructed cellular model, we then determined lower uptake of Bodipy-labeled C16:0 without any difference in the uptake of Bodipy-labeled C12:0. The content of intracellular triglyceride which was mainly synthesized by LCFA concomitantly lowered down. Using gene knock down and overexpression, FATP4 was confirmed to be responsible for LCFA uptake. Moreover, ERK1/2 inhibitor U0126 and PPARγ antagonist T0070907 revealed ETEC could initiate cascaded phosphorylation of ERK1/2 and PPARγ resulting in hindered expression of FATP4. These results indicate ETEC challenge will cause dysfunction in FATP4-dependent LCFA uptake by phosphorylation of ERK1/2 and PPARγ. Furthermore, intestinal uptake of MCFA is in a FATP4-independent manner which is not easily disturbed by ETEC.